Levels And Factors Influencing The Technical Efficiency Of Carrot Farming in East Java, Indonesia - Diyana, Farah Rosyidah; Hanani, Nuhfil; Shinta, Agustina (Agro Bali : Agricultural Journal, 2025)
Carrots are a horticultural agricultural product with good prospects for development in East Java with a harvest area of 4,495 Ha and production of 8,9847 Tons. Apart from that, the increase in carrot consumption figures increased from 2021 by 1,354 kg.capita-1.year-1 to 1,429 kg.capita-1.year-1 in 2022. However, the productivity of carrot farming in East Java experiences fluctuations every year, which is influenced by production factors, so it cannot keep up with ever-increasing demand. This research aims to determine the level of technical efficiency of carrot farming and the factors that influence it. The methods used are Data Envelopment Analysis (DEA) and Tobit regression. The research was conducted in Sumberbrantas and Wonokerso villages for 3 months, from July 2023 to October 2023. Sampling using the simple random sampling method. The research results show that carrot farming in East Java has still not reached the full level of technical efficiency, with an average VRS of 0.826. The opportunity to increase technical efficiency is 0.174 by improving the input combination to suit already technically efficient farmers. Factors that significantly influence the technical efficiency of carrot farming in East Java are land area, experience, and dummy land ownership status. Meanwhile, age, education and number of family dependents do not significantly influence the level of technical efficiency.